Persistence patterns of opioid use over three follow-up years: the difference between non-cancer and cancer pain - Abdullah Sani, Asween Rowena; Zin, Che Suraya; Mohamed, Abdul Hadi; Izat, Munira; Ng, Kim Swan (2018)
Persistence Patterns Of Opioid Use Over Three Follow-Up Years: The Difference Between Non-cancer And Cancer Pain